2018
DOI: 10.1371/journal.pone.0192774
|View full text |Cite
|
Sign up to set email alerts
|

Beyond monetary benefits of restoring sight in Vietnam: Evaluating well-being gains from cataract surgery

Abstract: A more holistic understanding of the benefits of sight-restoring cataract surgery requires a focus that goes beyond income and employment, to include a wider array of well-being measures. The objective of this study is to examine the monetary and non-monetary benefits of cataract surgery on both patients as well as their caregivers in Vietnam. Participants were randomly recruited from a Ho-Chi-Minh City Hospital. A total of 82 cataract patients and 83 caregivers participated in the survey conducted for this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Although some previous studies have evaluated the possible benefit of cataract surgery on depression 13 , 15 23 , the results are controversial as some of these studies indicated that the depressive symptoms did not improve after cataract surgery 13 , 21 , 22 . Moreover, most of these studies had follow-up periods of < 1 year 13 , 15 23 , and only one was a population based study 16 . Therefore, we conducted this 16-year nationwide cohort study to enhance the reliability and indicated that the risk of depression was reduced by 25% in the cataract surgery group compared with that in the non-surgery group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some previous studies have evaluated the possible benefit of cataract surgery on depression 13 , 15 23 , the results are controversial as some of these studies indicated that the depressive symptoms did not improve after cataract surgery 13 , 21 , 22 . Moreover, most of these studies had follow-up periods of < 1 year 13 , 15 23 , and only one was a population based study 16 . Therefore, we conducted this 16-year nationwide cohort study to enhance the reliability and indicated that the risk of depression was reduced by 25% in the cataract surgery group compared with that in the non-surgery group.…”
Section: Resultsmentioning
confidence: 99%
“…They also have a higher institutionalisation rate 26 and visual hallucination risk, which is known as Charles Bonnet syndrome 27 , 28 . Studies have shown improved quality of life, mental health, and economic state in patients following cataract surgery 15 , 29 . Therefore, future studies are required to develop a multifactor strategy for the prevention and management of depression in patients with cataract or visual impairment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering these findings, we assumed that the patient subjective happiness and sleep quality also may be better postoperatively. Feeny et al showed that in Vietnam cataract surgery provided benefits that included significant improvements in earnings, mobility, self-care, ability to undertake daily activities, self-assessed health and mental health, life satisfaction, hope, and self-efficacy 19 .…”
mentioning
confidence: 99%